PENGARUH PENERAPAN SURAT PEMBERITAHUAN MASA ELEKTRONIK (E-SPT) TERHADAP EFEKTIVITAS DAN KONTRIBUSI PENERIMAAN PAJAK PERTAMBAHAN NILAI (Studi Kasus Pada Kantor Pelayanan Pajak Pratama Kota Banda Aceh) - Jamiul khasanah; Lilis Maryasih (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2022)
Abstract The purpose of this study was to examine the effect of the application of the electronic period notification letter (e-SPT) on the effectiveness and contribution of Value Added Tax (VAT) receipts and to see the difference in receipt of the Periodic VAT SPT between before and after the e-SPT was issued. This study has a population of VAT receipts reports, while the sample from this study uses purposive sampling technique, so that samples are obtained in the form of VAT receipts reports before the application of the VAT Period e-SPT and VAT receipts reports after the application of the VAT Period e-SPTs. The results of this study stated that there was no effect of the application of electronic mass notification letters on the effectiveness and contribution of VAT receipts at KPP Pratama Banda Aceh City. Likewise, the different tests that have been carried out have shown that there is no significant difference in VAT reporting receipts both before and after the implementation of the VAT Period e-SPT. However, when viewed from the average VAT reporting receipts, there is a difference between before and after the application of the VAT Period e-SPT, namely an increase of 2,316 VAT Period SPT reporting receipts after the application of the VAT Period e-SPT. Keywords: Application of e-SPT Period of VAT, Effectiveness and Contribution of Value Added Tax revenue